STRATEGI PEMERINTAH DAERAH DALAM PENGEMBANGAN SUMBER DAYA MANUSIA DI BADAN KEPEGAWAIAN DAERAH KABUPATEN BANTAENG - Angreni, Anisa; Mappamiring, Mappamiring; Tahir, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out the planning, organizing, monitoring and assessment of local government strategies in developing human resources in the regional civil service agency Bantaeng Regency. This study used a qualitative research by using a descriptive type. The data analysis technique used word reduction, data presentation, and conclusion. Then this study was collected through observation, interviews, and documentation. The results of this study showed that human resources and skills improve. The target for developing the quality of employees was to improve the ability and technical skills to do work, to improve skills and leadership skills and to make decisions. and still needed to be improved.